The free vibration analysis of carbon nanotubes-reinforced deep conical shells with an intermediate ring support under various boundary conditions. (15th July 2022) - Hou, Suxia; Zheng, Yangning; Zandi, Yousef; Khadimallah, Mohamed Amine; Ebtekar, Arash
Abstract: This article explores the free vibration characteristics of a conical shell strengthened with intermediate ring. The system is thought to be made up of a linearly elastic nanocomposite that is reinforced with carbon nanotubes (CNTs). To get the effective material characteristics, the modified rule of mixtures is employed. To account for shear deformations and rotational inertias occurring across the depth of the shell, the first-order model of shells is combined with Donnell's classical kinematic constraints. Hamilton's principle is applied to construct the generic motion equations and their related boundary and compatibility constraints. The resulting set of equations is solved analytically in the structure's circumferential direction. Additionally, the generalized differential quadrature element (GDQE) algorithm is performed to discretize the radial motion equations. An eigenvalue issue is constructed with various edge conditions for the structure boundaries and compatibility conditions to investigate the vibration frequencies. After demonstrating the efficacy and accuracy of the current approach for applying functionally graded (FG) CNT reinforced composite (RC) cylindrical shells with intermediate circle support, several parametric investigations are conducted to determine the effect of the geometric and ingredient properties of FG-CNTRC conical shells. Highlights: Natural frequencies of FG-CNTRC conical shell. Application of solid ring supporter to control and change the free vibration. Implementing TE-GDQE method to solve the current problem. Applying suitable continuity conditions in the shell edges and ring location.